3D characterization of a Boston Ivy double-skin green building facade using a LiDAR system. (December 2021) - Pérez, Gabriel; Escolà, Alexandre; Rosell-Polo, Joan R.; Coma, Julià; Arasanz, Roger; Marrero, Bernat; Cabeza, Luisa F.; Gregorio, Eduard
Abstract: On the way to more sustainable and resilient urban environments, the incorporation of urban green infrastructure (UGI) systems, such as green roofs and vertical greening systems, must be encouraged. Unfortunately, given their variable nature, these nature-based systems are difficult to geometrically characterize, and therefore there is a lack of 3D objects that adequately reflect their geometry and analytical properties to be used in design processes based on Building Information Modelling (BIM) technologies. This fact can be a disadvantage, during the building's design phase, of UGIs over traditional grey solutions. Areas of knowledge such as precision agriculture, have developed technologies and methodologies that characterize the geometry of vegetation using point cloud capture. The main aim of this research was to create the 3D characterization of an experimental double-skin green facade, using LiDAR technologies. From the results it could be confirmed that the methodology used was precise and robust, enabling the 3D reconstruction of the green facade's outer envelope. Detailed results were that foliage volume differences in height were linked to plant growth, whereas differences in the horizontal distribution of greenery were related to the influence of the local microclimate and specific plant diseases on the south orientation. From this research, along with complementary previous research, it could be concluded that, generally speaking, with vegetation volumes of 0.2 m 3 /m 2, using Boston Ivy ( Parthenocissus Tricuspidata ) under Mediterranean climate, reductions in external building surface temperatures of around 13 °C can be obtained and used as analytic parameter in a future 3D-BIM-object. Highlights: There is a lack of 3D-BIM-objects relating to Urban Green Infrastructure. 3D characterization of a double-skin green facade has been conducted. The volume was measured on each facade orientation using an MTLS. Local microclimate and facade orientation influence the facade volume. Volumes around 0.2 m 3 /m 2 lead to an external building temperature reduction of 13 °C.